- Computer Science Engineering (CSE)
- Digital Electronics and Logic Design
- The expression is an ex...

Q. |
## The expression is an example of Commutative Law for Multiplication. |

A. | ab+c = a+bc |

B. | a(b+c) = b(a+c) |

C. | ab=ba |

D. | a+b=b+a |

Answer» C. ab=ba |

View all MCQs in:
Digital Electronics and Logic Design

- This is an example of a POS expression:
- The simplification of the Boolean expression (A'BC')'+ (AB'C)' is
- The Boolean expression A.B+ A.B+ A.B is equivalent to
- Simplify the Boolean expression F = C(B + C)(A + B + C).
- Simplify the following expression into sum of products using Karnaugh map F(A,B,C,D) = (1,3,4,5,6,7,9,12,13)
- Simplify the given expression to its Sum of Products (SOP) form Y = (A + B)(A + (AB)')C + A'(B+C')+ A'B+ ABC
- Write the expression for Boolean function F (A, B, C) = m (1,4,5,6,7) in standard POS form.
- The simplified form of the Boolean expression (X+Y+XY)(X+Z) is
- The output of the expression F=A+B+C will be Logic when A=0, B=1, C=1. the symbol ' + ' here represents OR Gate.
- the boolean expression AB'CD'is

Login to Continue

It will take less than 2 minutes

Report MCQ